Pancreatic Cancer and Primary Sjögren’s Syndrome: A Case Report - Oliveira, Daniela; Chaves, Vanessa; Martins, José Carlos; Vaz, Carlos; Bernardes, Miguel; Almeida, Jorge (Case Reports in Rheumatology, 2021)
Primary Sjögren syndrome (SS) is a chronic inflammatory systemic autoimmune disease with a high risk of malignancy development, namely, lymphoproliferative neoplasms. Few studies also reported a high risk of solid cancers; however, the coexistence of primary SS and pancreatic cancer has been rarely described. In this paper, we aim to describe a case of a 59-year-old woman who was an active smoker with sicca symptoms and symmetrical polyarthritis and was diagnosed with primary SS two years before the development of metastatic pancreatic adenocarcinoma. Despite institution of chemotherapy, the patient succumbed to the malignancy. Besides that, we explore the link between primary SS and solid cancers including the main predictors of malignancy and the role of primary SS as a paraneoplastic syndrome. Patients with primary SS should be closely monitored for malignancy, not only for hematological cancer, but also for solid tumors. Further research is necessary to understand which are the predictors of cancer proliferation in primary SS patients.